Protective effects of cerium oxide nanoparticles in grapevine (Vitis vinifera L.) cv. Flame Seedless under salt stress conditions - Gholamreza Gohari; Elnaz Zareei; Havzhin Rostami; Sima Panahirad; Muhittin Kulak; Habib Farhadi; Mojtaba Amini; Maria del Carmen Martinez-Ballesta; Vasileios Fotopoulos (Ecotoxicology and Environmental Safety, 2021)
High levels of soil salinity can cause substantial decline in growth and productivity of crops worldwide, thus representing a major threat to global agriculture. In recent years, engineered nanoparticles (NPs) have been deemed as a promising alternative in combating abiotic stress factors, such as salinity. In this context, the present study was designed to explore the potential of cerium oxide nanoparticles (CeO2NPs) in alleviating salt stress in grapevine (Vitis vinifera L. cv. Flame Seedless) cuttings. Specifically, the interaction between CeO2 NPs (25, 50 and 100 mg L−1) and salinity (25 and 75 mM NaCl) was evaluated by assaying an array of agronomic, physiological, analytical and biochemical parameters. Treatments with CeO2 NPs, in general, alleviated the adverse impacts of salt stress (75 mM NaCl) significantly improving relevant agronomic traits of grapevine. CeO2 NPs significantly ameliorated chlorophyll damage under high levels of salinity. Furthermore, the presence of CeO2 NPs attenuated salinity-induced damages in grapevine as indicated by lower levels of proline, MDA and EL; however, H2O2 content was not ameliorated by the presence of CeO2 NPs under salt stress. Additionally, salinity caused substantial increases in enzymatic activities of GP, APX and SOD, compared with control plants. Similar to stress conditions, all concentrations of CeO2 NPs triggered APX activity, while the highest concentration of CeO2 NPs significantly increased GP activity. However, CeO2 NPs did not significantly modify SOD activity. Considering mineral nutrient profile, salinity increased Na and Cl content as well as Na/K ratio, while it decreased K, P and Ca contents. Nevertheless, the presence of CeO2 NPs did not lead to significant alterations in Na, K and P content of salt-stressed plants. Taken together, current findings suggest that CeO2 NPs could be employed as promising salt-stress alleviating agents in grapevine.